OPTIMALISASI PEMANFAATAN KANTOR DESA SEBAGAI TEMPAT PELAYANAN ADMINISTRASI PEMERINTAHAN DESA DI DESA PEBAUN HILIR KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI TAHUN 2015 - Raca Zailani; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
In order to maintain the administration of the village administration performing well, of course, the village chief should be able to utilize the village office as the administrative services of the village administration, village office is the center of government and public services in the village. The purpose research is to examine the use of village office as a service of public administration Village in the Village Pebaun Hilir Sub district Regency Kuantan Kuantan Mudik Singingi 2015 and to know the utilization constraint village office as the administrative services of the village administration in the village of Pebaun Hilir Sub district Regency Kuantan Kuantan Mudik Singingi 2015.This research was conducted in the village of Pebaun Hilir Subdistrict Regency Kuantan Kuantan Mudik Singingi. The method used is a qualitative research, data collection techniques are interviews, observation and documentation. Based on the survey results revealed that Village Office Pebaun Downstream never be used again, because of a dispute between one of the residents as owners of land by the village government. Administrative services carried out in the home village of the chief. Constraints utilization village office as the administrative services Village Governance in Rural Pebaun Hilir District of Kuantan Mudik Regency Kuantan Singingi is not going to transfer ownership of the ownership or control of land legally by the village government, facilities and infrastructure are inadequate, such as the absence of PLN, desk, office chairs and filing cabinets.Keywords: Village Office, Administrative services.